Understanding the milky way halo through large surveys - Koposov, Sergey (2009)
This thesis presents an extensive study of stellar substructure in the outskirts of the Milky Way(MW), combining data mining of SDSS with theoretical modeling. Such substructure, either bound star clusters and satellite galaxies, or tidally disrupted objects forming stellar streams are powerful diagnostics of the Milky Way's dynamics and formation history. I have developed an algorithmic technique of searching for stellar overdensities in the MW halo, based on SDSS catalogs ...